2015 ASEE Annual Conference and Exposition Proceedings
DOI: 10.18260/p.24316
|View full text |Cite
|
Sign up to set email alerts
|

Instructional Videos in an Online Engineering Economics Course

Abstract: The use of video lectures is a common method of delivering course content in online learning environments. Over time, our understanding of what makes an effective online video has evolved with advances in educational research and technology. In the past decade, free online video services such as YouTube have allowed widespread dissemination of instructional videos. Prevalence of high-quality instruction produced by organizations such as Kahn Academy has advanced our knowledge of effective video techniques and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…Some studies have shown videos less than 10 minutes in length are best, 1,8 while others have found that even shorter lengths, 5 minutes, are better for understanding information based on quiz scores. 9 Since these studies were often for videos of full lectures, the lower end of the video lengths are probably most appropriate for lab equipment or software. A detailed analysis of video lengths found that many students use YouTube speed acceleration features to limit the time spent on videos.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Some studies have shown videos less than 10 minutes in length are best, 1,8 while others have found that even shorter lengths, 5 minutes, are better for understanding information based on quiz scores. 9 Since these studies were often for videos of full lectures, the lower end of the video lengths are probably most appropriate for lab equipment or software. A detailed analysis of video lengths found that many students use YouTube speed acceleration features to limit the time spent on videos.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Videos should be a cohesive collection of concepts told in a logical narrative that highlights the most important concepts. 9,11 An effective video is broken into segments to organize material in an understandable format. Spoken word, pictures, and text should be combined to convey more than each could alone; in particular, the use of a real person in the video makes it easier for students to pay attention.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Case studies are rarely used (less than 18% of the faculty surveyed utilized case studies) in the teaching tool box [9] - [11] even though case studies allow students to gain insight into the theoretical principles being presented in the class room via their practical applications described in the case studies. Curriculum enrichment has also been attempted via instructional videos [12], additional readings and writing research papers [13] and design based problem solving approach [14].…”
Section: Introduction and Rationalementioning
confidence: 99%
“…Textbook publishers may provide supplemental video content to complement hard-copy or electronic textbooks [5]. Some streaming platforms like YouTube provide opportunities for educational videos [6] and [7]. These platforms offer instructional videos covering general topic overviews to very specific college coursework.…”
Section: Introductionmentioning
confidence: 99%